The lost art of stratigraphy? A consideration of excavation strategies in Australian indigenous archaeology. Issue 3 (1st September 2016) - Ward, Ingrid; Winter, Sean; Dotte-Sarout, Emilie
Abstract: Archaeological interpretation is increasingly an interdisciplinary effort between archaeologists and specialists of various archaeological sciences. In such integrated work, excavation data are the primary reference to provide context for the vast range of cultural and biological material that are later investigated. A review of over three decades of published Australian archaeological data shows that there is a widespread practice in the use of arbitrary excavation units, not only as excavation tools but also as analytical units. Building from the lectures of Smith on the Lost Art of Stratigraphy and other published literature, this paper explores some of the issues surrounding different excavation strategies applied today, particularly in Australian prehistoric archaeology, and the implications and impacts on interpretation of archaeological and palaeoenvironmental results. It is argued that, while arbitrary excavation is appropriate in certain circumstances, the best method for excavation, sampling and interpretation of archaeological sites is by stratigraphic context because it provides a more precise understanding of the original depositional context and what that might tell us about past environment and past human behaviour.